An emerging Panton-Valentine leukocidin-positive CC5-meticillin-resistant Staphylococcus aureus-IVc clone recovered from hospital and community settings over a 17-year period from 12 countries investigated by whole-genome sequencing - Aloba, B K; Kinnevey, P M; Monecke, S; Brennan, G I; O'Connell, B; Blomfeldt, A; McManus, B A; Schneider-Brachert, W; Tkadlec, J; Ehricht, R; Senok, A; Bartels, M D; et al. (The Journal of hospital infection, 2023)
BACKGROUND: A novel Panton-Valentine leukocidin (PVL)-positive meticillin-resistant Staphylococcus aureus (MRSA) clonal complex (CC)5-MRSA-IVc ('Sri Lankan' clone) was recently described from Sri Lanka. Similar isolates caused a recent Irish hospital outbreak. AIM: To investigate the international dissemination and diversity of PVL-positive CC5-MRSA-IVc isolates from hospital and community settings using whole-genome sequencing (WGS). METHODS: Core-genome single nucleotide polymorphism (cgSNP) analysis, core-genome multi-locus sequence typing (cgMLST) and microarray-based detection of antimicrobial-resistance and virulence genes were used to investigate PVL-positive CC5-MRSA-IVc (N = 214 including 46 'Sri Lankan' clone) from hospital and community settings in 12 countries over 17 years. Comparators included 29 PVL-positive and 23 PVL-negative CC5/ST5-MRSA-I/II/IVa/IVc/IVg/V. RESULTS: Maximum-likelihood cgSNP analysis grouped 209/214 (97.7%) CC5-MRSA-IVc into Clade I; average of 110 cgSNPs between isolates. Clade III contained the five remaining CC5-MRSA-IVc; average of 92 cgSNPs between isolates. Clade II contained seven PVL-positive CC5-MRSA-IVa comparators, whereas the remaining 45 comparators formed an outlier group. Minimum-spanning cgMLST analysis revealed a comparably low average of 57 allelic differences between all CC5/ST5-MRSA-IVc. All 214 CC5/ST5-MRSA-IVc were identified as 'Sri Lankan' clone, predominantly spa type t002 (186/214) with low population diversity and harboured a similar range of virulence genes and variable antimicrobial-resistance genes. All 214 Sri Lankan clone isolates and Clade II comparators harboured a 9616-bp chromosomal PVL-encoding phage remnant, suggesting both arose from a PVL-positive meticillin-susceptible ancestor. Over half of Sri Lankan clone isolates were from infections (142/214), and where detailed metadata were available (168/214), most were community associated (85/168). CONCLUSIONS: Stable chromosomal retention of pvl may facilitate Sri-Lankan clone dissemination.
Keywords: Methicillin-Resistant Staphylococcus aureus; exotoxiny; Staphylococcal Infections; Exotoxins; Leukocidins; methicilin; leukocidiny; multilokusová sekvenční typizace; methicilin rezistentní Staphylococcus aureus; mikrobiální testy citlivosti; stafylokokové infekce; Multilocus Sequence Typing; Hospitals; Humans; lidé; Microbial Sensitivity Tests; Methicillin; nemocnice